2022
DOI: 10.18502/ijpa.v17i3.10629
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Intestinal Parasitic Infections among Patients Visiting a Referral Hospital in Tehran Province, Iran

Abstract: Background: Intestinal parasitic infections (IPIs) are still considered a public health problem of mankind, particularly in immunocompromised patients. We aimed to determine the prevalence of IPIs with an emphasis on immunocompromised patients in a referral hospital in Tehran Province, Iran. Methods: In this cross-sectional study, 442 fecal specimens were collected randomly from patients, referred to Baqiyatallah Hospital in Tehran Province, Iran from May to September 2020. The collected specimens were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Based on our findings, the frequency of IPIs in the age group 60–69 years was 26.1% higher than in other age groups, possibly due to the low personal hygiene and education level of older people and lack of awareness of the transmission of IPIs. Nevertheless, there was no significant correlation between the frequency of IPIs and age groups, consistent with other reported studies ( 13 , 16 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Based on our findings, the frequency of IPIs in the age group 60–69 years was 26.1% higher than in other age groups, possibly due to the low personal hygiene and education level of older people and lack of awareness of the transmission of IPIs. Nevertheless, there was no significant correlation between the frequency of IPIs and age groups, consistent with other reported studies ( 13 , 16 ).…”
Section: Discussionsupporting
confidence: 92%
“…According to our knowledge, this research was the first attempt to illustrate the frequency of IPIs in this area. This finding was similar to a study performed in Tehran in which the prevalence of IPIs was reported as 17% among patients visiting a referral hospital ( 16 ). In addition, the prevalence of the intestinal parasite in people referred to different medical laboratories in Babol was 12.1% ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations